Capitalismo global y cambio educativo. Los fundamentos estructurales e ideológicos de la política educativa neoliberal - Guillermo Miranda-Camacho (Universidad Nacional, Costa Rica, 2004)
The reconfiguration of the social and political hegemony of the capital consolidated with the union of the New Right (neoliberals and neoconservatives) was a reaction against the crisis of capital accumulation that took place during the early 1970´s. The strategic objetives the this hegemonic block were basically the re-establishment of globalized capitalism and the establishment of a neoliberal political and cultural hegemony. This essay provides an hermeneutic approach to show that the irruption of educational discourse and the neoliberal education policy are essential elements of the political and economical program promoted by the New Right as a way to face the following structural changes: the regulated crisis of capitalist accumulation that began in 1973; the crisis of legitimation and rationality of the State of contentment; the dismantling of the Keynesian pact and the sociodemocrat agreement in postwar education; the economical restructuring opposite to the acumulation crisis; the imperatives of configuration, introduction and legitimation of the new social structure of global capitalist accumulation and the consolidation of neoliberalism`s hegemonic culture.